DEBT POLICY ANALYSIS AS A MEDIATION OF FINANCIAL DISTRESS PREDICTIONS FOR COMPANIES REGISTERED AT THE JAKARTA ISLAMIC INDEX (JII) IN 2013-2016 - Witri Aulia Maudy; Hendri Tanjung (State Institute of Islamic Studies (IAIN) Palu, 2018)
This study aims to determine the effect of Debt Policy (DER) on Financial distress (Altman Z-score Modification) and the influence of Managerial Ownership (MOWN), Dividend Policy (DPR), Profitability (ROA), Liquidity (CR), Company Size (SIZE), to the Debt and Financial distress Policy. This paper also looks the indirect effect of Debt to Financial distress Policy. The data is analyzed by using path analysis. Based on the Lisrel output results, the covariance matrix of path model estimation is not statistically different from the sample data covariance matrix. The population in this research is companies, which are registered in JII period 2013-2016. By judgment sampling technique, only 20 companies are obtained. Total data of this research is 80 company data. This study finds that debt policy is negatively significant to Financial distress. Managerial ownership and liquidity do not significantly affect debt policy. Dividend policy, profitability, and company size have no effect on debt policy. On the other hand, Managerial Ownership, Dividend Policy, Profitability and Company Size as a whole affects the Financial distress. However, simultaneously Managerial Ownership, Dividend Policy, and Company Size are negatively insignificant, while Profitability and Liquidity have a positive effect although not significant to Financial distress company. From the calculation of direct and indirect influence, it is known that the indirect influence is bigger than direct influence.